Oral plasmablastic lymphoma as the first manifestation of AIDS - Daniela Assis do Vale; Carolina Martelli Rogado; Danielle Lima Corrêa de Carvalho; Marilia Trierveiler; Karem López Ortega (Sociedade Brasileira de Dermatologia, 2017)
Abstract Plasmablastic lymphoma is a non-Hodgkin lymphoma characterized by its plasmacytic differentiation and predilection for the oral cavity. It is among the lymphomas most commonly associated with AIDS. This report details a case of a HIV-positive patient with a 1-month history of an exophytic mass in the gingival area of the upper left quadrant. The diagnosis of plasmablastic lymphoma was made based on its histopathological and immunophenotypical features. She was treated with chemotherapy followed by autologous hematopoietic stem cell transplantation. Despite complete resolution of the lesion, the patient died of cardiorespiratory arrest. This case illustrates plasmablastic lymphoma as the first clinical manifestation of AIDS, highlighting the importance of differentiating between a potentially malignant lesion and other pathologic processes.